EMPLOYEE MAPPING IN SUPPORTING JOB PROMOTION - Zahara Tussoleha Rony (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
In recent years, the development of the health insurance business, in recent years since 2019 in Indonesia has decreased, including one insurance company X. The company closed several branches in several cities in Indonesia. Many employees are forced to take early retirement decisions and resign, but on the other hand, potential employees are still needed to become branch heads. Several branch heads who have retired must be replaced with new ones, therefore, the company needs to carry out several strategies to get new branch head candidates. This study aims to explain a process of mapping the head of an insurance company branch carried out by the human resources division. The research method used is qualitative with a case study approach. Informants in this study were prospective branch heads, consultants, and the human resources team. From the results of this study, the mapping system carried out by the Human Resources Division in mapping is quite effective. The selection of test tools and dimensions of managerial competence used for prospective branch heads is quite by the profile and branch leadership needs. This research can improve the mapping skills of branch heads of similar insurance companies and contribute knowledge of human resource management for insurance companies and other similar companies.